The strategic teacher as becoming of classroom environment. (European Journal of Education and Psychology, 2011)
The aim of this paper is contributing to the proposition that a strategic teacher is a different and effective way to contribute to improving the classroom climate. An experimental situation was proposed to train a group of teachers in motivating teaching skills through learning strategies based on instruction, assessment, social skills and motivation. It was carried out by secondary teachers from several schools who taught classes to 264 high school students in first grade and 253 in third grade. The instrument used to measure the classroom climate was the Classroom Environment Scale (CES), taking six of the suggested variables: Involvement, Teacher support, Task orientation, Competition, Order and organization and Innovation. The results point out efficacy of the program in third grade in all the variables, compared to the results of first grade that only improve in Competition and Innovation. Regarding gender, no differences were found in first grade. However, there are more efficacy of the program in women of third grade in Self-efficacy of performance, just the opposite that in Involvement, Teacher Support and Order and Organization. With regard to grades, an improvement is produced in third grade in the variables of Involvement, Task orientation and Order and organization that doesn’t occur in first grade.